The Dimensions of Territorial Embeddedness of the Business Services Sector in Central and Eastern Europe - Geodecki, Tomasz (Journal of Public Governance, 2021)
Objective: The purpose of this article is, first, to propose a range of measures of territorial embeddedness in order to describe the phenomenon in question, and, second, to use the se measures to determine the level and dynamics of the embeddedness of the Business Services Sector (BSS) in Central and Eastern European (CEE) economies.Research design & Methods: In the debate about the future of the BSS in these low-cost economies, two challenges have been identified. The first one involves the threat of relocation. The other one is associated with linkages between service companies and local customers/suppliers weaker than that of in Western Europe. These two challenges can be addressed by tackling the third one, namely the increasing of process efficiency. In consequence, even an increased share of foreign contractors does not have to reduce the scale of cooperation with local entities. In the empirical part of this paper, changes in these three areas that make up territorial embeddedness are explored in depth. Eight divisions covering the BSS in the CEE-11 countries were compared with their Western European counterparts (the EU-17) at two points in time, i.e. in 2000 and in 2014. The study relies on basic statistical data and calculations with the use of the World Input-Output Tables.Findings: It was found that due to productivity growth, the cost competitiveness of the BSS in CEE countries wasmaintained in the period of interest. Moreover, despite the growing internationalisation of the sector, the scaleof cooperation of the BSS with local actors has increased. The rapidly improving skills of employees in the Central European BSS – as well as the growing importance of knowledge-intensive services (KIS) in the structure of value added – can further contribute to the importance of CEE as a location for business services in Europe.Implications/Recommendations: The studied period saw an improvement in the structure of value added, as an increasing share of it was accounted for by knowledge-based services. This implies a high probability of further productivity growth of the BSS in CEE, and bodes well for the degree of territorial embeddedness both in terms of decreasing the likelihood of relocation and amplifying the capacity of local actors to act as the suppliers and the recipients of state-of-the-art services.Contribution/Value Added: I have recognised that when service provision is subject to massive offshoring, it is not so much the intensity of service provision (exports) as the intensity of value added creation in the local economy that is of significance. Moreover, the relative gains in this respect should determine the scale of territorial embeddedness, the competitiveness of individual sectors, as well as their growth prospects.